Driving the nation, balancing life: A review of work-life balance among loco-pilots in India - Ranjan, Rajesh; Singh, Rashmi; Tripathi, Saumya (Edelweiss Applied Science and Technology, 2026)
The entire psychosocial working environment for loco pilots (railway train drivers) in India is extremely demanding, isolating, and devoid of socialization. In addition, loco pilots are subject to a great deal of responsibility to be on time and safe. There are few opportunities for personal freedom due to the rigorous schedules and technical constraints, which include the kind of trains and route configurations. Long work hours, strange and inappropriate schedules, and heavy workloads all contribute to the workload, which can lead to serious work-family conflicts. The paper examines work-life quality among Indian Railway train drivers, identifies primary conditions underpinning the problem of work-life imbalances, and clarifies the possible impact on the well-being of drivers and safety in their activities. It considers the applicable concepts regarding work-life balance and studies the impact of working conditions on the well-being of loco pilots, which in turn has an impact on the efficiency and development of the Indian Railways. This study also has theoretical implications for organizations’ policies and practices, particularly as the experiences of railway drivers can inform new organization-wide work/life integration policies. The advantages of having a happy and healthy workforce are passed on to both passengers and employees through increased productivity at the workplace, reduced employee absence, and fewer accidents. Subsequently, the enhancement of WLB among railway drivers could be an important source of future research and concern, as it can result in a less hazardous and more efficient experience with the use of public transportation.